Windows XP pocket reference - Karp, David A. (O'Reilly, 2003)
Windows XP Pocket Reference is a handy book for power users and system administrators who need a solid reference with quick answers, but not a lot of explanation. This book is a powerful tool that quickly covers XP's applications and tools, tasks and settings, and commands. Windows XP Pocket Reference covers the following topics:Getting StartedMouse and Keyboard ShortcutsComponents of Windows XPSetting LocatorRegistry TweaksCommand Prompt & Recovery ConsoleError MessagesPacked with information in an easy-to-read format, Windows XP Pocket Reference is perfect for someone familiar with Windows w.